Environmental health disparities and maternal and child health: applying the life course approach - Wakeel, Fathima; Njoku, Anuli (Handbook of Social Sciences and Global Public Health, 2023)
Mounting evidence suggests that differential environmental exposures significantly contribute to a wide range of population health disparities. Adopting a life course approach to maternal and child health enables readers to uncover the mechanisms by which prenatal and early life environmental exposures potentially shape both short- and long-term physical and mental health outcomes. This chapter applies the life course approach to explore the adverse influences of environmental risk factors on maternal and child health. The following four case studies will be discussed: (1) the pervasive impacts of secondhand smoke; (2) the deleterious effects of lead exposure; (3) the development of asthma; and (4) the potential origins of autism spectrum disorder. The chapter also provides recommendations for programmatic and policy interventions to reduce the prevalence of four salient environmental hazards, including secondhand smoke, lead, air pollution, and pesticides, as well as proposed future directions in research regarding these exposures.
Keywords: Asthma; Autism spectrum disorder; Environmental health justice; Health equity; Lead exposure; Life course approach; Maternal and child health; Secondhand smoke exposure; dept.pch